Recontamination in food processing - Aantrekker, Esther den (Wageningen Universiteit, 2002)
The work described in this thesis contributes to the reduction in the lack of recontamination models by quantifying biofilm formation and air recontamination. The application of the models in two example production processes showed that they can be incorporated in MRA to determine its importance and estimate the probability of becoming ill after consumption of the food item.